إعادة الاعتبار من خلال عملية ترميم و إعادة تأهيل المصليات الجنائزية بقصر غرداية - قمر الطيقان, ابراهيم; Zebda, Amira, Directeur de thèse (My University, 2019)
The funerary chapels of Ghardaia Palace are considered one of the most important historical monuments and popular souvenirs by certain customs and traditions practiced and by its architecture in harmony with the climatic nature of the region It is also a cultural heritage of UNESCO that is not known at the national and international levels and remains confined to the popular memory of the M’Zab Valley, which is justified by its degraded state. As it suffers recently from the degradation of its architectural and cultural value, it is necessary to intervene to rehabilitate it by a process of restoration of these mosques to the original situation and the definition of this cultural heritage at the local and regional level. Global order to preserve them, they must be activated and ensure the sustainability of their use through the programming of a tourist route combining the different monuments while preserving the social and cultural privacy of the region
Laghouat : Université Amar Telidji - Département d'architecture Option : Architecture et patrimoine